Technology-Related Business Disruption in the Indian Aerospace Sector - Joseph, Jofy (Digital Repository of Theses, 2026)
The aerospace industry in India is changing due to recent policy changes, and entry into the industry by the private sector, although, regulatory barriers, certification and a fragmented supplier base are threatening to restrain the adoption of technology predictably. The gap that this thesis will fill the issue of perception of regulation as a self- restrictive phenomenon, and a reproducible framework in order to predict and handle the disruptive change in the aerospace ecosystem of India. This study adopts a comprehensive research approach that integrates dynamic policy simulation, value-chain mapping, and policy Analysis. Primary data are drawn from purposive surveys with regulators, original equipment manufacturers, startups, and suppliers; these sources set up the simulations and shape standard evaluation criteria. Sensitivity and robustness tests assess policy interventions and indicate the strength and the relative impacts of model changes. The findings prove that regulatory and institutional forces play a significant role in the implementation of new technologies. Simulations reveal that long approval timelines, ambiguous evaluation criteria, and unclear liability regimes constitute the most significant bottlenecks, creating a “liability of disruption” for new entrants and increasing risks further down the supply chain. The gains in speed of approval and legal predictability create greater and more enduring gains in the survival of startups and market access compared to capacity expansion. Reliance on imports and one-supplier systems continue to enhance the effects of regulatory delays. The study concludes that effective aerospace innovation in India requires coordinated reforms that coordinate clear regulations, sufficient certification, strong supply chains, and skilled workers. The thesis contributes theoretically by including how regulations are designed and how institutions function into models of how new ideas spread, and practically by providing a reproducible framework for policy testing and decision support. While limitations related to targeted sampling and simulation assumptions remain, using multiple methods and reliability checks support practical, policy-related findings to help India compete globally in aerospace. Key words: Space economics, Aerospace innovation, Disruptive change, Policy simulation, Value chain mapping, Regulatory barriers, Technology adoption.